TINGKAT PEMAHAMAN DAN FAKTOR KEPATUHAN MINUM OBAT ARV PADA PASIEN HIV/AIDS - Adib Samudra Putra; Saepuddin Saepuddin; Suci Hanifah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
Patients with HIV/AIDS require long-term therapy, so adherence is a significant thing that needs attention. aim of this article review is to find out the Level of Understanding and Compliance Factors in Taking ARV Medication in HIV/AIDS Patients. The research was conducted in November 2022 by searching for Indonesian articles related to article reviews with the year of publication 2017-2022 in the Google scholar database using the keyword